Measurement and improvement of emergency department performance through inspection and rating: an observational study of emergency departments in acute hospitals in England. Issue 6 (3rd April 2019) - Allen, Thomas; Walshe, Kieran; Proudlove, Nathan; Sutton, Matt
Abstract : Introduction: Hospital inspection and the publication of inspection ratings are widely used regulatory interventions that may improve hospital performance by providing feedback, creating incentives to change and promoting choice. However, evidence that these interventions assess performance accurately and lead to improved performance is scarce. Methods: We calculated six standard indicators of emergency department (ED) performance for 118 hospitals in England whose EDs were inspected by the Care Quality Commission, the national regulator in England, between 2013 and 2016. We linked these to inspection dates and subsequent rating scores. We used multilevel linear regression models to estimate the relationship between prior performance and subsequent rating score and the relationship between rating score and post-inspection performance. Results: We found no relationship between performance on any of the six indicators prior to inspection and the subsequent rating score. There was no change in performance on any of the six indicators following inspection for any rating score. In each model, CIs were wide indicating no statistically significant relationships. Discussion: We found no association between established performance indicators and rating scores. This might be because the inspection and rating process adds little to the external performance management that EDs receive. It could also indicate the limited ability of hospitals to improve ED performance because of extrinsic factors that are beyond their control.